First-hand experiences of belonging among child refugees and asylum seekers, post-migration: a meta-synthesis - Trotter, Emily F.; Woodcock, Kate A. (Frontiers in Psychology, 2025)
IntroductionRefugees and asylum seekers represent a growing population worldwide, of which almost half are children. Child refugees are especially vulnerable and marginalised, yet research into refugee experiences infrequently captures their voices. Establishing a sense of belonging is a particularly pertinent issue for young refugees; however, the processes supporting belonging are poorly understood. This meta-synthesis collated the findings of qualitative studies that explored first-hand experiences of belonging among child refugees and asylum seekers, post-migration, with the aim of better understanding the processes that facilitate a sense of belonging in this population.MethodsSystematic searches of four electronic databases: PsycINFO, Web of Science, PubMed, and Education Resources Information Centre [ERIC], identified 1,192 primary studies, of which eight were included for meta-synthesis. An integrated qualitative appraisal checklist was used to assess quality of the studies (American Psychological Association, 2018; National Institute of Health and Care Excellence, 2012). The analysis was subsequently guided by Noblit and Hare’s (1988) seven-phase methodology.ResultsOne overarching theme was interpreted from the analysis: Migratory Loneliness and Societal Isolation. This underpinned three themes which described the processes facilitating a sense of belonging: Experiences of Inclusion and Support, Family Connectedness, and Adaptive Responses to Resettlement.DiscussionFindings are discussed in relation to existing research, and clinical implications considered. The study offers insights into the nuances of refugee children’s lived experiences, alongside recommendations for the construction of safe and inclusive spaces where children feel visible. An individualised approach to working with newly resettled children is also advocated.